Functional Surfaces in Biology Little Structures with Big Effects Volume 1 - Gorb, Stanislav N. (Springer Netherlands : Imprint: Springer, 2009)
This book is devoted to the rapidly growing area of science dealing with structure and properties of biological surfaces in their relation to particular function(s). This volume, written by a team of specialists from different disciplines, covers various surface functions such as protection, defense, water transport, anti-wetting, self cleaning, light reflection and scattering, and acoustics. Because biological surfaces have a virtually endless potential of technological ideas for the development of new materials and systems, inspirations from biology could also be interesting for a broad range of topics in surface engineering.